How the Interval between Prime and Boost Injection Affects the Immune Response in a Computational Model of the Immune System. (11th September 2012) - Castiglione, F.; Mantile, F.; De Berardinis, P.; Prisco, A.
Abstract : The immune system is able to respond more vigorously to the second contact with a given antigen than to the first contact. Vaccination protocols generally include at least two doses, in order to obtain high antibody titers. We want to analyze the relation between the time elapsed from the first dose (priming) and the second dose (boost) on the antibody titers. In this paper, we couple in vivo experiments with computer simulations to assess the effect of delaying the second injection. We observe that an interval of several weeks between the prime and the boost is necessary to obtain optimal antibody responses.